General geology and structural analysis of Kemubu-Jelawang, Kelantan - Rubiah Ahmad (2016)
Kemubu-Jelawang is located in Kuala Krai district nearby Dabong town in southern part of Kelantan which is about 55 from kilometres from Jeli town passing through main road to Dabong. Geologically, the study area is bounded by Stong Complex from the Main Range Granite. In general, the study area cut cross from west to east of central belt in South Kelantan. The study area consist of some rocks type which are granite, sandstone, limestone and phylite. Instrusive rock granite included in formation of Stong Complex while sandstone, limestone and phylite correlated with Gua Musang Formation. One of the research objectives for this study is to generate geological map of the study area. The geological study of research area was completed by field work, sampling of outcrop and laboratory work for process doing thin section and map by using GIS. Geomorphology analysis was completed by doing topographic map, drainage map and detailed explain about weathering process at the study area. Another objective for this research study is to identify type of structural geology and analysis the structural geology by using rose diagram and stereonet method. The rose diagram and stereonet is drawn to illustrate the result of maximum and minimum stress forces that affected by the motion of plate tectonic and also correlated with lineament features. The overall result of lineament features analysis shows the orientation of maximum stress force coming from N-E and S-W is same with orientation of maximum stress force for joint analysis. While for dynamic analysis for normal fault showed the extensional force, σ³ are positioned at S-E and N-W quadrant same with quadrant orientations minimums stress force, σ³ of lineament. Lastly, for folding analysis showed the stress force causes the motion of rock and rock deform as fold. It proved that the structural geology was deformed cause by the tectonic movement.